Emerging incidence trends of eosinophilic esophagitis over 25 years: Results of a nationwide register‐based pathology cohort. Issue 7 (10th January 2021) - de Rooij, Willemijn E.; Barendsen, Marielle E.; Warners, Marijn J.; van Rhijn, Bram D.; Verheij, Joanne; Bruggink, Annette H.; Bredenoord, Albert J.
Abstract: Rationale: Eosinophilic esophagitis (EoE) has emerged from a case‐reportable illness in the early 1990s to a distinct clinicopathological entity. Increasing worldwide incidences have been observed, although due to various study designs estimates are inconsistent. Aim: To determine population‐based annual incidence rates over a time period of 25 years. Methods: A nationwide register‐based pathology (PALGA) search was performed to identify reports describing esophageal eosinophilia between 1995 and 2019. EoE was identified if the diagnosis was confirmed by the pathologist. Crude incidence rates were estimated by the number of new EoE cases per year and matched with population data. Results: Between 1995 and 2019, 7361 unique patients' reports mentioned esophageal eosinophilia, of these 4061 were classified as EoE (71% male, mean age 37.9 ± 18.4 years). In total, 639 (16%) children (<18 years) were diagnosed. The EoE incidence increased from 0.01 in 1995 (95% CI: 0.0 – 0.04) to 3.16 (95% CI: 2.90 – 3.44) per 100.000 inhabitants in 2019. EoE was significantly more prevalent in males (OR 2.48 | 95% CI: 2.32 – 2.65; vs. females p  < 0.001) and adults (OR 1.42 | 95% CI: 1.31 – 1.55; vs. children p  < 0.001). Highest incidences were observed in 2019, being 4.37 (95% CI: 3.94 – 4.84) vs. 1.97 (95% CI: 1.68 – 2.29) per 100.000 males and females, respectively ( p  < 0.001). No seasonal variation was observed. Conclusion: Over the past quarter century, the annual rates of newly diagnosed EoE patients raised dramatically and this increase has not reached a deceleration yet. Abstract : Xxxxxx